New Analysis Procedures for Giving Feedback to Swimming Coaches and Swimmers - Sanders, R. H. (coachesinfo.com, 2002)
The purpose of this paper is to present some new ideas with respect to analysis of mid-pool, starts, and turns of swimmers. Mid-pool analysis has traditionally adopted a 'stroke length-stroke frequency' approach. However, the factors that influence stroke length and stroke frequency are indirect and not clearly evident. Therefore, variables that might logically contribute to performance are often overlooked. An alternative approach is to identify 'critical features' that arise directly from consideration of mechanical principles. Thus, variables that are likely to directly influence the propulsive and resistive impulse are identified. In this way the performance can be 'explained' rather than merely 'described' and training to change these variables can lead to improved performance. In turns, variables that affect the 'time in', 'time contact' and 'time out' are identified as important. These include variables that affect propulsive impulse applied to the wall, resistance after pushing off the wall, and the time when kicking becomes propulsive rather than increasing resistance. In dive starts variables that affect the time on the blocks, time to entry, and time below the surface are identified. Similar to turns, variables include those that affect propulsive impulse applied to the blocks, resistance during and after entry, and the time when kicking becomes propulsive rather than increasing resistance. (siehe auch unter http://www.coachesinfo.com/category/papers_and_abstracts_from_conference_proceedings_and_sports_science_journals/133/)